EXPLORING CSR REPORTING PRACTICES AND STRATEGIC FUND ALLOCATION IN PALM OIL COMPANIES - Dara Angreka Soufyan; Rimal Mahdani; Hafizhah Risnafitri; Abrar Amri; Dewi Maya Sari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Corporate Social Responsibility (CSR) has become a mandatory practice for companies, including those in the palm oil industry, which plays a significant role in the global economy. However, inconsistent accounting treatments for CSR expenditures have raised challenges in achieving transparency and accountability. This study examines the variations in CSR accounting practices among palm oil companies listed on the Indonesia Stock Exchange and their implications for financial transparency, stakeholder trust, and corporate sustainability. The findings reveal that companies adopt diverse approaches to reporting CSR expenditures, treating them as operating expenses, tax-related costs, or long-term investments. While some companies integrate CSR into sustainability initiatives aligned with global standards like ISPO and RSPO, others treat CSR as a compliance obligation. This inconsistency underscores the absence of explicit accounting standards for CSR, creating challenges for investors, auditors, and policymakers in assessing the impact of CSR activities. This study highlights the need for harmonised regulations and standardised CSR reporting practices to enhance financial transparency and accountability. By addressing these gaps, companies can strengthen stakeholder trust, improve corporate reputation, and contribute to the long-term sustainability of the palm oil industry.